2018
DOI: 10.14689/ejer.2018.74.8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between School Principals’ Leadership Behaviors and Teachers’ Organizational Trust

Abstract: Purpose: A comfortable and happy work environment, where all the teachers are sincere and true to each other and sure that what they say and do will not be used against them, is a basic need for a teacher. It is thought that meeting this expectation is up to the feeling of trust, especially in the principal, and then in colleagues and students and parents. The aim of the study is to reveal the relationship between school principals' leadership behaviors and teachers' organizational trust, and at what level lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…Öztürk and Aydın (2012) stated that teachers working in secondary education institutions have a high level of trust in the institution and the communication dimension is important. Kars and Inandı (2018) noted that administrators should deal with the problems of teachers and be more transparent and decisive in their actions to create a sense of trust in the school. According to the findings of our research, it is believed that the coexistence of teachers who teach in different branches due to the type of educational institution of high school teachers, communication is stronger and the emphasis on teachers' feelings and thoughts within the institution will determine the relationship of organizational trust with job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Öztürk and Aydın (2012) stated that teachers working in secondary education institutions have a high level of trust in the institution and the communication dimension is important. Kars and Inandı (2018) noted that administrators should deal with the problems of teachers and be more transparent and decisive in their actions to create a sense of trust in the school. According to the findings of our research, it is believed that the coexistence of teachers who teach in different branches due to the type of educational institution of high school teachers, communication is stronger and the emphasis on teachers' feelings and thoughts within the institution will determine the relationship of organizational trust with job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on leadership styles in schools have revealed that authentic leadership style (Bird, Wang, Watson & Murray (2009), school principal's leadership style (Hallinger & Walker, 2015;Kars & Inandi, 2018), and ethical leadership Cemaloglu & Kilinc, 2012) are associated with teachers' trust levels.…”
Section: Principalmentioning
confidence: 99%
“…It could be used by the academic community for further research on DSL and its relationship with other relevant school elements. Furthermore, because many research results show that the development of DSL could have multiple positive effects on teachers (Johnson, 2017; Kars and Inandi, 2018; Peker et al, 2018; Shepherd-Jones and Salisbury-Glennon, 2018), students (Mager and Nowak, 2012; Quinn and Owen, 2016) and the school as a whole (Delgado, 2014; Dorczak, 2014; Gülbeher, 2016), the instrument could be used by school leaders for self-evaluation and as a basis for further school leadership development. Because there is a lack of autonomy in Croatian schools with regard to shared leadership, the results of the research in which the instrument was used could be an evidence-based starting point for decision-makers to effect changes in relation to Croatian educational policy and legislation.…”
Section: Discussionmentioning
confidence: 99%